An Analysis on Compliment Responses in English among Javanese People - Arum Sekar Nurhijannah (Institut Agama Islam Negeri (IAIN) Manado, 2021)
The study aims at exploring the differences of compliment responses in English among Indonesian males and females. The study consists of 20 English learners in University State of Yogyakarta. The participants are expected to respond five scenarios in a modified Discourse Completion Test (DCT). The participants’ responses are submitted to SPSS and Paired Samples T-Test is applied. It reveals that each scenario has different responses but it doesn’t have significant difference among male and female participants in responding the compliments. Both male and female participants tend to agree the compliment using appreciation token.